Juridical Analysis Of Personnel Dispute Resolution In The State Administrative Court (Analysis Of Case Decision Number 45/G/2020/Ptun-Jkt) - Indy Setiawan, Hatta; Abustan, Abustan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Juridical settlement of personnel disputes according to Law No. 5 of 2014 concerning the State Civil Apparatus is resolved through administrative remedies, consisting of administrative objections and appeals. Personnel dispute resolution is resolved through the State Administrative Court, while in Law No. 5 of 2014, personnel dispute resolution is resolved through administrative efforts consisting of administrative objections and appeals. Based on this, the legal protection provided by Law No. 5 of 2014 against the State Civil Apparatus in dispute reduces the procedural rights of the State Civil Apparatus,because it can no longer defend its rights to the judiciary. Law enforcement carried out by judges in examining and trying case No. 45/G/2020/PTUN-JKT., is in accordance with legal provisions as specified in the PTUN Law. Based on the examination before the court, it was revealed that the legal facts that the defendant had issued a decree on the object of dispute, namely the Decree of the Governor of DKI Jakarta No. 1616 of 2019 concerning the imposition of severe disciplinary punishment in the form of dishonorable dismissal of non-permanent employees on behalf of Susanto at Satpol. PP. not in accordance with the principle of presumption of innocence, the Defendant has also issued a decision on the object of dispute not in accordance with the basic regulations that authorize the Defendant so that in substance the decision of the object of dispute contains juridical reproach. One of the resolutions of disputes according to Islamic law is the courts (Al-qadha). Etymologically, Al-qadha means to decide to establish. While terminologically, Al-qadha is a judicial institution tasked with delivering binding legal decisions. The postulates about qadha' are quite numerous in QS. Al-Baqarah (2) verse 213.